The Effect of Training Using (Plume-Shoe - Rubber Bands) on Explosive Power and Enzyme (CPK-LDH), Accuracy and Aiming With a Three-Point Jump for Young Basketball Players - Abdel Nabi Mohamed Hewitt, Mohamed; Abdel-Nabi Mohamed Hewitt, Nour (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to identify the effect of training using the plastic shoe (rubber bands) in the explosive and enzymatic capacity (CPK-LDH) and the accuracy and correction of the three-point jump for young basketball players, and the researcher adopted the experimental research method on a sample of Mahmoudiyah Sports Club for youth. The number of individuals in the sample reached 12 players, which were divided into two groups so that the first group is trained on the palladium shoes and rubber bands, and the second group uses the exercises prepared by the coach for the period from 10/4/2018 to 10/6/2018, and after applying the tests Physical, physiological, and skilled in research and implementation of exercises prepared by the researcher and conducting post-tests, the results of which were statistically processed using the Statistical Bag System for Social Sciences (SPSS) version (V24), as the researcher concluded that it is possible to reach that the exercises using plastic shoes and rubber bands Contributed to the development of explosive power and enzyme (CPK-LDH) accuracy and correction by jumping three points for basketball players.